Water excellent solvent for the synthesis of bifunctionalized cyclopentenones from furfural. Issue 22 (28th September 2017) - Nardi, M.; Costanzo, P.; De Nino, A.; Di Gioia, M. L.; Olivito, F.; Sindona, G.; Procopio, A.
Abstract : The transformation of furfural into functionalized cyclopentenone derivatives is a smart process to advance the sustainable synthesis of important chemicals from biomass. Abstract : Chiral cyclopentenones are important precursors in the asymmetric synthesis of target molecules. In particular, C-2 amino cyclopentenones could be utilised as intermediates towards antitumor natural products. On the basis of our previous experience, we report an environmentally friendly protocol for the synthesis of bifunctionalized cyclopentenones in water from furfural. The use of water and MW gives high regioselectivity and good to excellent yields. The reaction can be realized in short times with various nucleophiles.